Innovative cleaner production technique: foam glass production from lead crystal glass sludge - ElKersh, Hussein Abdel Fattah (AUC Knowledge Fountain, 2014)
An innovative cleaner production technique that adopts open-recycling system of the grinding and polishing sludge of lead crystal glass was applied in this study. Foam glass with good properties that can be used in the thermal insulation applications was produced from the grinding and polishing sludge. The leaching test of the sludge showed that it is a hazardous waste because its leachate has a lead concentration of 7.5 mg/l, while the leachate of the produced foam glass was proved to have a negligible lead concentration of less than 0.02 mg/l. The effect of the heating method, sintering temperature, holding time and additives of Silicon Carbide SiC and granite powder on the properties of the foam glass was investigated. The investigated properties are foam bulk density, porosity percentage, compressive strength and thermal conductivity. Sintering the samples by direct insertion to the oven resulted in lower compressive strength and lower density compared to the low heating rate of around 1.5 oC/min adopted in this study. Sintering temperature of 750 oC at a holding time of 30 minutes produced foam glass with bulk density of 0.485 g/cm3, porosity of 84.6%, compressive strength of 2.21 MPa and thermal conductivity of 0.051 W/m. K. These properties are comparable to those of commercial foam glass. Lower temperatures resulted in foam glass with significantly higher bulk density, while higher temperatures led to deterioration in the foam glass properties due to the coalescence phenomenon. The addition of SiC leads to increase foam glass porosity and reduce its bulk density, compressive strength and thermal conductivity. Adding SiC from 2 to 8 wt.% produced a foam glass with porosity 89.4-91.9%, bulk density 0.256-0.334 g/cm3, compressive strength 0.89-1.44 MPa and thermal conductivity 0.039-0.058 W/m.K. In contrast, the addition of granite powder reduces the foam glass porosity and increases its bulk density, compressive strength and thermal conductivity. Adding granite powder from 2 to 8 wt.% produced a foam glass with porosity 76.1-83.2%, bulk density 0.529-0.747 g/cm3, compressive strength 2.43-5.09 MPa, thermal conductivity 0.074-0.135 W/m. K. It can be concluded that the foam glass prepared by adding SiC is suitable to the applications that need very low thermal conductivity, while the foam glass prepared by adding granite powder is suitable to the applications where compressive strength is of more importance.